Microtubules Are Essential for Mitochondrial Dynamics–Fission, Fusion, and Motility–in Dictyostelium discoideum - Woods, Laken C.; Berbusse, Gregory W.; Naylor, Kari (Frontiers in Cell and Developmental Biology, 2016)
Mitochondrial function is dependent upon mitochondrial structure which is in turn dependent upon mitochondrial dynamics, including fission, fusion, and motility. Here we examined the relationship between mitochondrial dynamics and the cytoskeleton in Dictyostelium discoideum. Using time-lapse analysis, we quantified mitochondrial fission, fusion, and motility in the presence of cytoskeleton disrupting pharmaceuticals and the absence of the potential mitochondria-cytoskeleton linker protein, CluA. Our results indicate that microtubules are essential for mitochondrial movement, as well as fission and fusion; actin plays a less significant role, perhaps selecting the mitochondria for transport. We also suggest that CluA is not a linker protein but plays an unidentified role in mitochondrial fission and fusion. The significance of our work is to gain further insight into the role the cytoskeleton plays in mitochondrial dynamics and function. By better understanding these processes we can better appreciate the underlying mitochondrial contributions to many neurological disorders characterized by altered mitochondrial dynamics, structure, and/or function.